Transformation of flood risk management with evolutionary resilience - Herath HMM; Wijesekera NTS (E3S Web of Conferences, 2020)
The occurrence of flood disasters has become a vicious problem in many urban regions. Operationalization of flood resilience has become a significant concern with the increase of urban development and climate change. The objective of this paper is at first to analyze how flood resilience has been framed over the past period of time. Second, this paper has focused to identify the practical difficulties related to the available flood risk assessment and management frameworks for operationalization of flood resilience. The results show that the flood risk and resilience has been framed differently throughout the time, in diverse perspectives but still remains as contested concepts. Evolutionary resilience has been reframed the flood risk management system as an integrated and adaptive system with the recognition of the uncertainties due to the dynamics of socio-spatial interdependencies of flood risk. Therefore, the integration and the adaptive capacity of spatial planning has become a crucial aspect for operationalizing flood resilience which is governed through the knowledge base of the dominant discourses of stakeholders and the way of power and the resource exercised in the context.